Brand Faith: How Spiritual Relationships Develop Between Consumers and Brands - Ryu, Kyungin; Miller, Elizabeth G; Godfrey, D Matthew (Journal of Consumer Research, 2026)
Abstract Consumers increasingly seek spiritual satisfaction and existential meaning through brands. However, despite the rising prominence of secular forms of spirituality, consumer–brand relationship research largely overlooks the processes by which consumers initiate, develop, and maintain spiritual connections to brands. Using the concept of faith as a theoretical lens, this article explores how consumer–brand relationships take on spiritual dimensions. Drawing on an interpretive biographic analysis of in-depth interviews and netnographic data, the authors examine spiritual relationship development processes as they unfold between consumers and brands over time. Findings identify five phases of brand faith development (intuition, association, reflection, affirmation, and universalization), which progress from initial attraction to deep conviction. Consumers cultivate faith in brands across these phases through a process of believing in, valuing, and committing to a brand as a sacred entity that acts as a center of spiritual meaning. These findings offer a more nuanced understanding of spiritual relationships between consumers and secular brands than current literature provides. The analysis also examines factors that facilitate or inhibit brand faith development, contributing a contextual understanding of brand faith that accounts for influences arising from an interplay between personal, brand, and marketplace factors that affect consumer spirituality.